Fuzzy relational database model and managemant system for imprecise information - Nguyen, Hoa; Nhi, Nguyen Thi Uyen; Duy, Le Nhat (Journal of Computer Science and Cybernetics, 2021)
This paper introduces a fuzzy relational database model (FRDB) and the management system for it. FRDB is built by extending the classical relational database model with the fuzzy membership degree of tuples in relations. The management system for FRDB with the querying language like SQL is built by using a classical open-source management system.